Study Of Vernacular Spaces (Case Study: Contemporary Javanese House) - Loebis , Moehammed Nawawiy; Nuraini , Sarika (Jurnal Koridor, 2019)
As the development era, vernacular architecture in a traditional Javanese house transformed into a contemporary Javanese village of Meranti Aek Nabara. Physical changes occur in spatial patterns beyond is the management of the front page, back, and sides, while the spatial pattern in is the type and quantity of space, an organization of space, orientation, and patterns of circulation. The purpose of this research is to find out the changes and the causes of such changes, aspects influenced. The research was carried out with the observation in the field, and in-depth interviews with respondents. Research methods a descriptive qualitative approach. On the management front page, the side and rear and spatial patterns in, almost all occurring changes.